The Turkstream Pipeline and Its Impact on Turkiye-Russia Energy Relations - ÜNSAL, GAMZE (İstanbul Kültür Üniversitesi, 2022)
The need for energy is growing every day in the modern world. As this requirement grows, so does the countries' dependence on energy, which increases the cost of energy importation for those countries. This thesis is based on the relations between Türkiye and Russia in light of the political and economic indicators centered on the TurkStream and its energy dependence. In this study, recent Türkiye-Russia energy relations are examined from the perspective of interdependence. The role of energy in Türkiye-Russia political relations and the importance of the TurkStream project will be discussed. The relations between Türkiye-Russia are improving, especially in the energy sector and the general economy. In this regard, the interdependence approach has been used to examine Türkiye's geographical importance, rising energy needs, and mutual economic interest/benefit variables between the two countries. In addition, this thesis will also examine how political problems affect the relations between Türkiye and Russia. Energy cooperation between Türkiye and Russia has improved despite political problems from time to time. This thesis will analyze how Türkiye-Russia relations are affected by the TurkStream project and whether these relations can continue in the future from a liberal perspective based on the theory of interdependence. This thesis will be a scenario for Türkiye-Russia relations in the future.
Türkakım Doğal Gaz Boru Hattı ve Türkiye-Rusya Enerji İlişkisine Etkisi
▪ Yüksek lisans tezi.